CASE REPORT : OSTEOARTHRITIS - Imayati, Putu; Kambayana, Gede (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Osteoarthritis is a degenerative joint disease in which the affected joint is usually the large joint and unilateral. Prevalence of osteoarthritis in Indonesia, 15.5% in men and 12.7% in women, where the incidence is increasing with age. Osteoarthritis is more common an idiopathic disease or unknown cause although there is also a secondary cause such as trauma, infection, neurological or metabolic disorders. The usual complaints that perceived by osteoarthritis patients is pain in the affected joint, especially after the load on the joint. Therapy in osteoarthritis is usually symptomatic, which include the control of risk factors, physiotherapy and pharmacological. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Osteoarthritis, joint disease